2015
DOI: 10.1111/vde.12244
|View full text |Cite
|
Sign up to set email alerts
|

Gene transcription of pro‐inflammatory cytokines and chemokines induced by IL‐17A in canine keratinocytes

Abstract: Keratinocytes activated by IL-17A have the ability to produce various pro-inflammatory cytokines and chemokines, suggesting that IL-17A may play a central role of the development of Th2-associated inflammation in canine AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…40 IL-17 activates canine keratinocytes to produce several pro-inflammatory cytokines and currently it is speculated to have an important role in the development of a Th2 response. 58 The link between keratinocyte-derived cytokines is demonstrated by increased expression of TSLP 59 and IL-33 in canine atopic skin. 1 Increased expression of IL-33 can have negative consequences on the function of tight junction proteins such as claudin.…”
Section: The Role Of the Microbial Composition Of Atopic Skinmentioning
confidence: 99%
“…40 IL-17 activates canine keratinocytes to produce several pro-inflammatory cytokines and currently it is speculated to have an important role in the development of a Th2 response. 58 The link between keratinocyte-derived cytokines is demonstrated by increased expression of TSLP 59 and IL-33 in canine atopic skin. 1 Increased expression of IL-33 can have negative consequences on the function of tight junction proteins such as claudin.…”
Section: The Role Of the Microbial Composition Of Atopic Skinmentioning
confidence: 99%
“…Real-time RT-PCR was performed on genes encoding canine IL-4, IL-5, IL-13, INF-c and TNF-a using Thermal Cycler Dice Real-Time System II (Takara Bio Inc.) and SYBR Premix Ex Taq II (Takara Bio Inc.). 15,16 Three canine genes, CG14980, RPL32 and RPS18, were selected as reference genes. 16 PCR reactions were performed at 95°C for 10 s, followed by 47 cycles at 95°C for 5 s and 60°C for 30 s, with a final extension at 95°C for 15 s, 60°C for 30 s and 95°C for 15 s. The relative expression ratio was measured using the comparative threshold cycle (Ct) and the 2 -DDCt method.…”
Section: Real-time Qrt-pcrmentioning
confidence: 99%
“…These results suggest that GM‐CSF production in CPEK activated via PAR‐2 may be regulated not only by NFAT, but also by another transcription factor, such as nuclear factor‐kB (NF‐kB) or activator protein‐1 (AP‐1). A recent study demonstrated that IL‐17A, a typical Th17 cytokine, also induced the transcription of gm‐csf in CPEK . A number of clinical trials targeting GM‐CSF are underway in humans with rheumatoid arthritis, multiple sclerosis, asthma and plaque psoriasis, but not AD …”
Section: Keratinocyte‐derived Chemokines and Cytokines That Are Direcmentioning
confidence: 99%
“…A recent study demonstrated that IL-17A, a typical Th17 cytokine, also induced the transcription of gm-csf in CPEK. 95 A number of clinical trials targeting GM-CSF are underway in humans with rheumatoid arthritis, multiple sclerosis, asthma and plaque psoriasis, but not AD. 86 Thymic stromal lymphopoietin (TSLP) Thymic stromal lymphopoietin (TSLP) was first identified as a stimulator of B cell development in the culture supernatant of a murine thymic stromal cell line.…”
Section: Keratinocyte-derived Cytokines and Chemokinesmentioning
confidence: 99%